3D printing: a useful tool for the fabrication of artificial electromagnetic (EM) medium. Issue 2 (21st March 2016) - Tian, Xiaoyong; Yin, Ming; Li, Dichen
Abstract : Purpose: Artificial electromagnetic (EM) medium and devices are designed with integrated micro- and macro-structures depending on the EM transmittance performance, which is difficult to fabricate by the conventional processes. Three-dimensional (3D) printing provides a new solution for the delicate artificial EM medium. This paper aims to first review the applications of 3D printing in the fabrication of EM medium briefly, mainly focusing on photonic crystals, metamaterials and gradient index (GRIN) devices. Then, a new design and fabrication strategy is proposed for the EM medium based on the 3D printing process, which was verified by the implementation of a 3D 90o Eaton lens based on GRIN metamaterials. Design/methodology/approach: A new design and manufacturing strategy driven by the physical (EM transmittance) performance is proposed to illustrate the realization procedures of EM medium based device with controllable micro- and macro-structures. Stereolithography-based 3D printing process is used to obtain the designed EM device, an GRIN Eaton lens. The EM transmittance of the Eaton lens was validated experimentally and by simulation. Findings: A 3D 90o Eaton lens was realized based on GRIN metamaterials structure according to the proposed design and manufacturing strategy, which had the broadband (12-18 GHz) and low loss characteristic. The feasibility of 3D printing for the artificial EM medium and GRIN devices has been verified for the further real applications in the industries. Originality/value: The applications of 3D printing in artificial EM medium and devices were systematically reviewed. A new design strategy driven by physical performance for the EM device was proposed and validated by the firstly 3D printed 3D Eaton lens.